7 T MRI reveals diffuse iron deposition in putamen and caudate nucleus in CADASIL. Issue 12 (25th August 2012) - Liem, Michael K; Lesnik Oberstein, Saskia A J; Versluis, Maarten J; Maat-Schieman, Marion L C; Haan, Joost; Webb, Andrew G; Ferrari, Michel D; van Buchem, Mark A; van der Grond, Jeroen
Abstract : Objective: Diffuse iron deposition in the brain is commonly found in older people. One of the possible mechanisms that contribute to this iron deposition is cerebral small vessel disease. The aim of this study is to quantify diffuse iron deposition in patients with the hereditary small vessel disease cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL). Methods: 25 NOTCH3 mutation carriers and 18 healthy controls were examined using high-resolution T2*-weighted imaging on a 7 T whole body MRI scanner. Susceptibility-weighted MRI scans were analysed for areas of signal loss and increased phase shift. Phase shift measurements in deep grey nuclei, cortex and subcortical white matter were compared between mutation carriers and controls. For confirmation, ex vivo brain specimens from another three patients with CADASIL were analysed for iron deposition using ex vivo MRI combined with iron histochemistry. Results: In vivo MRI showed areas of decreased signal intensity and increased phase shift in mutation carriers. Compared with healthy controls, mutation carriers had significantly higher phase shift in the putamen (p=0.0002) and caudate nucleus (p=0.006). Ex vivo MRI showed decreased signal intensity in the putamen and caudate nucleus in all specimens. Histochemistry confirmed the presence of iron deposition in these nuclei. Conclusions: This study demonstrates increased diffuse iron accumulation in the putamen and caudate nucleus in patients with the small vessel disease CADASIL. This supports the hypothesis that small vessel disease contributes to the process of increased iron accumulation in the general population.